Biomarker‐adapted treatment in high‐risk large B‐cell lymphoma - Leppä, Sirpa; Meriranta, Leo; Arffman, Maare; Jørgensen, Judit; Karjalainen‐Lindsberg, Marja‐Liisa; Beiske, Klaus; Pedersen, Mette; Drott, Kristina; Pasanen, Annika; Karihtala, Kristiina; Mannisto, Susanna; Wold, Bente; et al. (Wiley, 2025)
Survival rates for patients with high-risk large B-cell lymphoma (LBCL), particularly those with biological risk factors, remain inadequate. We conducted a biomarker-driven phase II trial involving 123 high-risk patients aged 18–64 with LBCL. Based on their biological risk profiles, patients received either R-CHOEP-14 (without risk factors) or DA-EPOCH-R-based regimens (with risk factors). Biological high-risk factors included C-MYC translocation, C-MYC and BCL2 co-translocation, 17p/TP53 deletion, co-expression of MYC and BCL2, and P53 and/or CD5 immunopositivity. Additionally, we evaluated circulating tumor DNA (ctDNA) kinetics during therapy. Sixty-one patients (50%) were classified into biologically high-risk group. Three-year failure-free survival and overall survival rates for the entire study population were 79% and 88%, respectively. DA-EPOCH-R did not improve survival compared to our previous trial, where patients with the same biological risk factor criteria received R-CHOEP-14-based therapy. High pretreatment ctDNA levels, 17p/TP53 deletion, and TP53 mutations were associated with worse outcomes. In contrast, ctDNA negativity at the end of therapy (EOT) was indicative of a cure and effectively addressed false residual PET positivity. The findings demonstrate promising survival for high-risk LBCL patients, aside from those with TP53 aberrations, high ctDNA levels, and/or EOT ctDNA positivity.